'A Word to Start an Argument with': Virginia Woolf's Craftsmanship. Issue 1 (2nd January 2021) - Peat, Alexandra
Abstract: This paper explores Virginia Woolf's 1937 radio broadcast (and later essay) 'Craftsmanship' in the context of craft culture. As Woolf considers the word judiciously and playfully throughout 'Craftsmanship', it becomes a nexus point for an entanglement of ideas around making, creating, and producing. This paper places Woolf's understanding of craft practices in the context of contemporary debates regarding the legacy of the arts and crafts movement, Roger Fry's work in the Omega Workshops, and her own experience in the Hogarth Press. While it is tempting to see the Hogarth Press as a model of craft culture, Woolf was sceptical about any nostalgia for craft practices, often rather sloppy with the craft of book making, and deeply ambivalent about any valorization of craft. Without dismissing the significant place of the Hogarth Press in discussions about craft culture, this paper is most interested in Woolf's repeated use of 'craft' to talk about the work of the writer. It explores Woolf's own ambivalent engagement with writing as 'craft' and questions what it might mean to see Woolf as a craftswoman. It pays attention to her suspicion of privileging 'well made' writing over imagination and emotion, her attitudes towards the professionalism of craft (particularly in the context of gender), as well as the often permeable boundaries between her 'craft' and her 'art'. For Woolf, the troublesome word 'craft' leads to, associates with, and intersects with concepts central to her life and work, including art, imagination, inspiration, production, process, amateurism, professionalism, education, skill, and vocation.